Imposto sobre Serviços de Qualquer Natureza (ISS): injuridicidade na importação e na exportação de serviços - Melo, Fábio Soares de (2020)
The purpose of this study is to examine the legal legitimacy of the incidence of the Tax on Rendered of Services (ISS), in the import of services and in the export of services, due to the examination of the legal rules included in the Federal Constitution of 1988 in the legislation complementary, distinct doctrinal positions and divergent jurisprudential manifestations. In the export of services, we will investigate the tax treatment related to the ISS in the hypotheses of “services provided entirely outside the country”; “service fully provided in the country”; and in the case of “services partially developed in the country and partially abroad”, seeking the appropriate legal meaning of the expression “result of the service”. In terms of the import of services, we will analyze the discipline related to the incidence of ISS on the “service from abroad”; and in the “service whose provision has started abroad”, and, in this second hypothesis, we will examine the legal nature of the “stage” developed by the foreign service provider in Brazil and the respective legitimacy of incidence. In view of the relevance of examining documents related to service import and service export, we will present a procedure to verify the elements essential to the identification of the appropriate tax treatment related to ISS (incidence, non-incidence or exemption)